The Impact of Electric Vehicle on Road Transportation in Indonesia: Energy Demand and CO2 Emission - Arif Yulianto Widi Kurniawan; Ahmad Agus Setiawan; Arief Budiman (JPSE (Journal of Physical Science and Engineering), 2020)
Light Duty Vehicle (LDV) for road transportation in Indonesia is the biggest energy consumption with most of the energy carriers from refined fuel oil with high CO2 emission. Battery Electric Vehicle (BEV) is one of the alternatives to reduce oil consumption and CO2 emission on the road transportation sector. This research is carried to analyse impact on BEV on energy demand and carbon emission. Modified Mobility Model (MoMo) with PUCE methods was developed to projecting road transportation demand in Indonesia. This research shows that road transportation will reach 519 MBoe in 2040 with 83.6% from refined fuel oil. With moderate EV, energy will be reduced by 31 MBoe (6%), and refined fuel oil reduced by 8.5%. With a high EV scenario, energy will be reduced by 57 MBoe (14%) and refined fuel oil reduced by 16%. CO2 emission will be reduced up to 4.8 to 8.8% in 2040.DOI: http://dx.doi.org/10.17977/um024v5i22020p036